Rapid and sensitive detection of Laem-Singh virus by reverse transcription loop-mediated isothermal amplification combined with a lateral flow dipstick - Narong Arunrut (2018)
Laem-Singh virus (LSNV) was discovered recently in Thailand in farmed Giant Tiger shrimp (Penaeus monodon) displaying signs of slow growth syndrome. Loop-mediated isothermal amplification (LAMP) allows DNA to be amplified rapidly at a constant temperature. Here a reverse transcription (RT)-LAMP method was combined with a chromatographic lateral-flow dipstick (LFD) to detect LSNV RNA rapidly and specifically. The reaction was optimized at 65 °C for 30. min and amplified DNA hybridized to an FITC-labeled oligonucleotide probe for 5. min was detected at LFD test line 5. min after application. Including 10. min for rapid RNA extraction, test results could be generated within 1. h and did not require electrophoresis. Compared to an existing RT-PCR method, the RT-LAMP-LFD was also ∼1000-fold more sensitive in detecting LSNV RNA. © 2011 Elsevier B.V.